Comparison between transdermal buprenorphine and intravenous paracetamol for post-operative analgesia after major plastic reconstructive surgery under general anesthesia – A randomized double-blind controlled trial - Arghya Maity; Rajasree Biswas; Suchismita Mallick; Ghosh, Sujata; Sarbari Swaika (Asian Journal of Medical Sciences, 2023)
Background: Adequate pain management is an essential entity in reconstructive surgery to prevent adverse physiological and psychological outcome. Transdermal buprenorphine has been mostly studied in chronic pain and cancer related pain but hardly studies in acute pain are available. Aims and Objectives: The aims of this study were to compare post-operative pain relief achieved by transdermal buprenorphine and IV paracetamol in terms of safety and efficacy. Sedation and adverse effects were also studied. Materials and Methods: This is a prospective, parallel group, double-blind, and randomized trial. After ethics, clearance and consent from 46 patients undergoing major reconstructive surgery were allotted into Group B, (n=23) who received transdermal buprenorphine and Group P (n=23) who received m IV paracetamol 6 hourly. IV Paracetamol was taken as active control. Standard institutional protocol for general anesthesia was followed. Visual analog scale (VAS) score was measured postoperatively for 48 h. Diclofenac sodium was the rescue analgesic. Sedation was assessed by Ramsay Sedation score. Results: Transdermal buprenorphine patch (TDB) gave superior pain relief in comparison to intravenous paracetamol 48 h postoperatively, P≤0.0.5 pin VAS score. The total amount of rescue analgesic required was high in Group P than Group B (P=0.034). Hemodynamic stability was better maintained with TDB with minimal sedation and side effect. Conclusion: TDB (20 μg/h; 20 mg) can be safely used for post-operative analgesia with greater efficacy and minimal side effects when compared to intravenous paracetamol.